2018
DOI: 10.5430/jnep.v8n8p34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concept mapping on problem solving skills, competence in clinical setting and knowledge among undergraduate nursing students

Abstract: Background and objective: Concept mapping is a powerful instructional tool in the clinical settings that improves competency of undergraduate nursing students in interprets situations, problem solving, decision making and critical thinking in different circumstances. Also enable them to provide optimal comprehensive care for clients. This study was conducted to evaluate the effect of concept mapping on problem solving skills, competence in the clinical settings and knowledge among undergraduate nursing student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
(26 reference statements)
1
16
0
3
Order By: Relevance
“…They expressed that using of concept map grasp the attention of the audience, acquire presentation and communication skills. These findings would be interpreted in the highlight of many studies that concluded that concept map allowed students to be engaged in the learning process and improved their critical thinking [53,54,55].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…They expressed that using of concept map grasp the attention of the audience, acquire presentation and communication skills. These findings would be interpreted in the highlight of many studies that concluded that concept map allowed students to be engaged in the learning process and improved their critical thinking [53,54,55].…”
Section: Discussionmentioning
confidence: 72%
“…These reputations of concept map were reported by many researchers who viewed the concept map as an educational method produced visual conceptualization that enhancing the learning process and acquiring problem-solving skills. In addition, they found the concept map provides an enjoyable learning environment that permits students to express their own ideas and intellectual capabilities [55,56,57,58]. Difficulty in constructing the design of concept map and time-consuming were among the disadvantages the students encountered in concept map application which is agreed with [20,59].…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, nursing students need broad-based preparations that include a wide scope of knowledge and skills from nursing and other related fields to meet the complex client needs. [5] Hadi et al (2015) explained that students' academic performance is affected by many factors, including motivation, which may be easily ignored. It is necessary, however, for nursing educators, managers and consultants to examine motivation in their students.…”
Section: Discussionmentioning
confidence: 99%
“…Thus focusing to the concept of motivation is very important in educational setting. [5] Learning Motivation in the present study was defined in terms of both intrinsic (pushed from in the learner) and extrinsic (teacher-and overall performance-pushed). [6] The four intrinsic factors are: First, the students' ideals in self-competency to examine and obtain; second, the students' techniques in being actively engaged whilst acquiring knowledge; third, the students' information-in search of curiosity in mastering, and fourth, the students' intrinsic motivation orientation directed to mastering and studying project dreams.…”
Section: Introductionmentioning
confidence: 99%
“…The concept map is an innovative method that will facilitate students' learning process (El-Hay, El Mezayen, & Ahmed, 2018;Rosciano, 2015). It should be supported by instructors and students as a learning method (Jaafarpour, Aazami, & Mozafari, 2016;Khrais & Saleh, 2017).…”
Section: Concept Mapmentioning
confidence: 99%